2012
DOI: 10.1371/journal.pone.0046802
|View full text |Cite
|
Sign up to set email alerts
|

Methylobacterium-Induced Endophyte Community Changes Correspond with Protection of Plants against Pathogen Attack

Abstract: Plant inoculation with endophytic bacteria that normally live inside the plant without harming the host is a highly promising approach for biological disease control. The mechanism of resistance induction by beneficial bacteria is poorly understood, because pathways are only partly known and systemic responses are typically not seen. The innate endophytic community structures change in response to external factors such as inoculation, and bacterial endophytes can exhibit direct or indirect antagonism towards p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
78
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 54 publications
3
78
0
6
Order By: Relevance
“…Since niche similarities can adversely impact coexistence (41), there may have been resource-related competition between the pathogen and other members of its bacterial class. Previous studies have also indicated Methylobacterium and Sphingomonas to be involved in protecting host plants from various pathogens (42)(43)(44)(45). Furthermore, by examining the year-long cooccurrence patterns for the 20 most abundant families and Liberibacter spp., we uncovered negative correlations between the pathogen and three bacterial families (Burkholderiaceae, Xanthomonadaceae, and Micromonosporaceae) that have previously been described to have plant-beneficial properties (18, 23, 27, 46).…”
Section: Discussionmentioning
confidence: 99%
“…Since niche similarities can adversely impact coexistence (41), there may have been resource-related competition between the pathogen and other members of its bacterial class. Previous studies have also indicated Methylobacterium and Sphingomonas to be involved in protecting host plants from various pathogens (42)(43)(44)(45). Furthermore, by examining the year-long cooccurrence patterns for the 20 most abundant families and Liberibacter spp., we uncovered negative correlations between the pathogen and three bacterial families (Burkholderiaceae, Xanthomonadaceae, and Micromonosporaceae) that have previously been described to have plant-beneficial properties (18, 23, 27, 46).…”
Section: Discussionmentioning
confidence: 99%
“…Endophytes establish a mutualistic symbiosis with their hosts because they are selectively favoured 3,4 . They are classified according to their colonization strategy.…”
mentioning
confidence: 99%
“…Facultative endophytes live in the soil and are able to colonize the plant when the opportunity arises. Passive endophytes colonize the plant through open wounds in the root hairs 3,5 . Endophyte community structure and composition are closely related to plant phenology, soil type, pH and bacterial density in the rhizosphere 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Under necessity, for example, under some external threat, the endophytic bacterial community can be mobilized by some external stimulus and rise a size of their populations [28,29,35]. Activating endophytic residents coincided with the better survival of potato vitroplants under post vitro conditions and this may serve as an in- The maximum quantum yield (Fv/Fm), the efficient quantum yield (Ô PSII ), the PSII maximum efficiency (Fv'/Fm'), the photochemical quenching direct preliminary evidence that resident endophytes invest in the immune response [36,37]. We can postulate that resident endophytic bacterial communities (as well as other endophytic microorganisms) have a potency to modulate the plant protection system against external threat.…”
mentioning
confidence: 99%